Ventilatory function in the Eisenmenger syndrome. Issue 3 (June 1979) - MacArthur, C G; Hunter, D; Gibson, G J
Abstract : Ventilatory function and carbon monoxide transfer factor were studied in nine adult patients with post-tricuspid intracardiac defects and the Eisenmenger syndrome. A consistent mild defect of ventilatory function was found, with raised residual volume and closing capacity and reduction of other lung volumes and maximal expiratory flows. Maximal expiratory flow was particularly reduced at low lung volumes. One of the four subjects in whom pressure-volume studies were performed showed loss of normal elastic recoil at low lung volumes. A significant poorly ventilated space was excluded since the volume of distribution of helium during a 10 second breath-hold at full inspiration was close to plethysmographically measured total lung capacity. Carbon monoxide transfer factor, after correction for haemoglobin concentration, was 77% of predicted normal values. Sequential assessment of carbon monoxide transfer factor might be useful in the early diagnosis of pulmonary vascular disease in infants with large intracardiac defects, since it is likely to be raised early due to high pulmonary blood flow and will fall with the development of pulmonary vascular disease.